Faktor-Faktor yang mempengaruhi Nominal Uang Rupiah yang Hilang di Kabupaten Ende - Valentin, Marselina; Penu, Yustina Paulina; Djata, Baltasar Taruma (JURNAL EQUILIBRIUM, 2023)
This study aims to determine the factors that affect the nominal rupiah lost in Ende Regency through data sourced from productive workers in Ende Regency. The variabels studied are inflation and public perception, both of which are independent variables. The formulation of the problem from this research is first, (1) how much is the effect of inflation on the nominal rupiah lost in Ende Regency? (2) how is the influence of public perception on the lost rupiah currency in Ende Regency? (3) what are the three factors that are more dominant in influencing the lost rupiah currency in Ende Regency? The analysis technique used in this study is multiple linear regression analiysis, the data must meet the basic assumptions, namely classical assumption test and hypothesis testing. The results of this study indicate that: First, the inflation variable does not have a positive effect on the nominal rupiah lost in Ende Regency. This is evidenced by the results of the individual significance test (t test). Value tcount>ttable (0,478<1.660). Both public perceptions have test (t test). The value of tcount>ttable (4,023>1,660). The third factor that is more dominant in influencing the nominal value of the lost rupiah in Ende Regency is public perception.